2021
DOI: 10.1155/2021/4163906
|View full text |Cite
|
Sign up to set email alerts
|

A Decision-Making Approach for Ranking Tertiary Institutions’ Service Quality Using Fuzzy MCDM and Extended HiEdQUAL Model

Abstract: The attainment of excellence in institutions is maintained through the institutions’ adherence to its core values and efficient service delivery. These factors are very important in facilitating global development of a country and determining the world ranking of an institution. To this effect, this study presents an effective approach for evaluating and ranking quality of services in a higher institution, taking four higher institutions in Nigeria as case studies. Service quality consists of different attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Firstly, these techniques provide a more comprehensive and balanced assessment of universities, considering multiple dimensions of performance and quality. This allows for a more accurate representation of universities' strengths and weaknesses, enabling stakeholders to make informed decisions based on a more complete picture [112]. Secondly, these techniques reduce the subjectivity in the ranking process by providing a structured framework for evaluating universities based on objective criteria [113].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, these techniques provide a more comprehensive and balanced assessment of universities, considering multiple dimensions of performance and quality. This allows for a more accurate representation of universities' strengths and weaknesses, enabling stakeholders to make informed decisions based on a more complete picture [112]. Secondly, these techniques reduce the subjectivity in the ranking process by providing a structured framework for evaluating universities based on objective criteria [113].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the AHP method appears, with 21 occurrences [6, 49-52, 55, 62, 64, 66, 67, 71, 77, 84, 90, 106, 121, 123, 127, 129, 134, 135]. In the third place, the fuzzy method [55, 58, 63, 72, 77, 87, 89-91, 96, 101, 114, 122, 124, 127, 129, 134] and TOPSIS method [50,51,55,59,67,80,84,90,97,103,104,108,118,125,127,129,134], with 17 occurrences each. In addition to those mentioned, the methods of the PROMETHEE family stand out with 9 occurrences [52,77,88,89,93,94,97,115,133].…”
Section: Figure 11 Word Cloudmentioning
confidence: 99%
“…Research conducted by (Tjahyadi et al, 2018), (Febriani et al, 2022) and (Oladipupo et al, 2021) using the HiEDQUAL (High Education Quality) approach found that service quality is an important concept in the higher education context which can affect student satisfaction with the services provided. In contrast to previous research, this study measures the level of student satisfaction with the quality of service at Bung Hatta University using the Importance Performance Analysis method by combining the HedPERF and HiEDQUAL approaches.…”
Section: Graph 1 Number and Percentage Of Inactive Students From 2015...mentioning
confidence: 99%